1990
DOI: 10.4315/0362-028x-53.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Petrifilm™ SM for the Enumeration of the Aerobic Flora of Fish

Abstract: Petrifilm™, developed by the 3M Laboratories, is a ready-to-use system for enumerating bacteria. Dry media and a cold water soluble gel are coated on films, thus eliminating the need to prepare media. The enumerations obtained by this technique were compared to the results obtained by the conventional pour plate technique on 130 samples of flesh from whole whitings and 98 samples of fillets of white fish. For fish fillets, the counts obtained by the two methods were comparable. In the case of the flesh from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Other studies have shown the repeatability of the PetrifilmT" ACP to be similar to, or better than, the standard method (Ginn et al 1984;Curiale et al 1989Curiale et al , 1990. A worse repeatability of the Petrifilml'" ACP, compared with the standard method, has been obtained for fish and has been attributed to the sporadic growth of a luminous marine bacterium on Petri-filmT" ACP that did not grow on the agar plates (Abgrall and Cleret 1990).…”
Section: Aerobic Colony Countmentioning
confidence: 99%
“…Other studies have shown the repeatability of the PetrifilmT" ACP to be similar to, or better than, the standard method (Ginn et al 1984;Curiale et al 1989Curiale et al , 1990. A worse repeatability of the Petrifilml'" ACP, compared with the standard method, has been obtained for fish and has been attributed to the sporadic growth of a luminous marine bacterium on Petri-filmT" ACP that did not grow on the agar plates (Abgrall and Cleret 1990).…”
Section: Aerobic Colony Countmentioning
confidence: 99%
“…Colour was measured using a Minolta CR‐300 Chromameter ( Minolta France , F‐78424 Carrieres‐sur‐Seine, France) and was expressed in the Lab scale (MacDougall, 1994) on mixed chicken skin and on raw sausage slices. Total viable counts (TVC), total coliforms (COL), Enterobacteriaceae (ENT) and Escherichia coli (EC) counts were measured using Petrifilm ( 3M Santé , F‐95029 Cergy‐Pontoise, France) rapid tests (Abgrall & Cleret, 1990). The number of colony forming units was noted N FL (CFU g −1 ), where FL is TVC, ENT, COL or EC.…”
Section: Analysesmentioning
confidence: 99%
“…But this study is contrary to finding from Europe and America. 8 This might be due to the cessation of short-term treatment that was commenced during pregnancy in Europe and America. The other possible explanation might be the death of a patient with lower CD4 count in Europe and America, about 427 patients died before developing events.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the rate of initial modification and interruption of treatment were high with in the first year after combination of Antiretroviral Therapy (cART) initiation. 8 Evidence shows that globally from 14.1% up to 47.7% patients changed their initial ART regimen from 2013 to 2018 9,10 and the rate of initial regimen change varies from 0.9 per 100 person-years up to 28.3 per 100 person-years of observations. 11,12 Different studies conducted in Ethiopia showed that initial regimen change among patients taking ART was 21-21.8% from 2014 to 2016.…”
Section: Introductionmentioning
confidence: 99%